Association of sella turcica bridging and morphologic characteristics with palatally impacted canine in lateral cephalograms - Nikoo Ghasemi; Soraya Akhoondi; Zohre Reyhani; Nima Motamed; Azin Nourian (University Library System, University of Pittsburgh, 2022)
Introduction: Researchers have been interested in the relationship between sella turcica bridging and various dental anomalies. This study investigates the association of sella turcica bridging and morphologic characteristics with the palatally impacted canine tooth. Materials and Methods:  Orthodontic records with high-quality lateral cephalometric and panoramic images were chosen. The study comprised 30 patients with palatally impacted canines (17 females and 13 males) and 30 controls with erupted canines (15 males and 15 females). The measurements were performed using the SCANORA 5.2.6 software. Further, the relevant data was collected and analyzed using SPSS software version 22. Descriptive statistical analysis was used to investigate data after their validation, with t-tests and chi-square tests to compare the two groups. The regression test was used to lessen the effects of confounding variables. Results: In the study group, 5 patients had type III sella turcica bridging, whereas 2 patients in the control group had type III sella turcica bridging. Results showed a statistically significant difference between the two groups (P-value=0.017). In the study group, the interclinoid distance and canine tooth angle were significantly lower than the control group (P-value=0.001, P-value=0.001). However, there were no significant differences in the depth and anterior-posterior diameter of sella turcica between the two groups (P-value=0.543, P-value=0.766). In terms of age (P-value = 0.400) and gender (P-value = 0.605), there was no significant difference between the two groups. Conclusions: The palatally canine impaction may be associated with the bridging of the sella turcica. Therefore, sella turcica bridging can be used as a diagnostic parameter for palatally canine impaction.